Entrepreneurial motivation and self-employment intention: Special reference to management undergraduates in jaffna district - Jasintha, N.; Renusha, V. (University of Jaffna, 2020)
This study aims to present the relationship between entrepreneurial motivations and self-employment intention among management undergraduates in the Jaffna district. A quantitative approach was utilized in this study. In the quantitative approach, the desirability of self-employment, tolerance for risk, planned behaviour and background factors were used as the independent variables to predict the self employment intention. It was examined in a convenient sampling of 154 management undergraduates at the University of Jaffna, from third and final year students with the structured questionnaire's help through which Findings have drawn for this quantitative analysis, the researcher has got 100 percent of the response. The entrepreneurial intention level of the management undergraduates and higher national diploma students is in the most substantial level. The students are interested in being their own boss, having desirability on self-employment, planned and systematic behaviour, and do not like to wait for the government job. Further, Entrepreneurial motivation contributes significantly to Self-employment intention and predicts acceptable percent of the variation found. Another significant limitation is that entrepreneurship is interrelated with environmental factors, economic issues and fiscal and monitoring portfolio which will not be examined in this research.
Keywords: Background factors; Desirability of self-employment; Planned behaviour; Self-employment intention and tolerance of risk